2010
DOI: 10.1007/s10147-010-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the fallopian tube

Abstract: Primary sarcoma of the fallopian tube is a very rare neoplasm. We report the case of a 69-year-old woman affected with leiomyosarcoma of the left fallopian tube. Her chief complaint was lower abdominal pain. The preoperative diagnosis was a left adnexal malignant tumor based on pelvic examination, abdominal computed tomography, and magnetic resonance imaging. Following a laparotomy, she was ultimately diagnosed with a FIGO IIc fallopian tube leiomyosarcoma. She was treated with total abdominal hysterectomy, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Immunohistochemical analysis forms an important part of the diagnostic work up of LMS to exclude potential morphologic mimics, including extragastrointestinal stromal tumors (6). Over the past 20 yr there have been seven publications describing 9 cases of PLFT confirmed by immunohistochemical analysis (Table 1) (5,(7)(8)(9)(10)(11)(12). The average age of onset of these cases was 51 yr with a range of 33 to 70 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis forms an important part of the diagnostic work up of LMS to exclude potential morphologic mimics, including extragastrointestinal stromal tumors (6). Over the past 20 yr there have been seven publications describing 9 cases of PLFT confirmed by immunohistochemical analysis (Table 1) (5,(7)(8)(9)(10)(11)(12). The average age of onset of these cases was 51 yr with a range of 33 to 70 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Although carcinosarcoma always occurs in postmenopausal women, the median age of incidence is 60 years old. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the surgical treatment of ovarian neoplasm, for the nonmetastasized tube LMS (FIGO I,II), the mainstay of operation is represented by complete resection (R0) consisting of peritoneal washing, inspection of peritoneum and the surface of abdominal organs, excision of all the abdominal masses, random biopsies, total abdominal hysterectomy, bilateral salpingo-oophorectomy, partial omentectomy, and pelvic and periaortic selective lymphadenectomy. For the metastasized tube LMS (FIGO III, IV), a debulking surgery should be considered in order to excise all the primary lesion and reduce the metastatic risks as much as possible many different regimens have been reported in published works, including acombination of ifosfamide with pirarubicin, [ 4 ] gemcitabin and docetaxel, [ 7 ] and DTIC-adriablastine-vincristine-cyclophosphamide schedule (CyVADIC). [ 8 ] Of note is the report by Kobayashi et al [ 6 ] involving a case of a stage IIIc patient who survived more than 6 years without any evidence of recurrence with intraperitoneal cisplatin followed by prolonged oral etoposide for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Even more uncommon are the soft tissue tumors of fallopian tube, and in most of the cases it is leiomyosarcoma. To the best of our knowledge, till date 39 cases of primary tubal sarcoma have been reported [1].…”
Section: Discussionmentioning
confidence: 99%
“…First case of pure sarcoma was described in 1886 by Senger et al Jacoby et al reported the 34th case of tubal sarcoma in 1993 and reviewed the previous reports [2]. The 39th case of primary tubal leiomyosarcoma was described by Ueda et al in 2009 [1].…”
Section: Discussionmentioning
confidence: 99%